The SysTrust's framework implementation as an internal control for assuring reliability of AIS and business performance: an integrated approach. (2018) - Al-Dmour, Ahmed Hani; Abbod, Maysam
This study aims to examine and validate the impact of the implementation of SysTrust's framework (principles and criteria) as an internal control method for assuring reliability of accounting information system on the business performance via the mediating role of the quality of financial reporting among Jordanian public listed companies based on the literature review and contingency theory; an integrated conceptual framework was developed to guide this study. The study's framework consists of three constructs: the SysTrust's service framework, the business performance and the quality of financial reporting. Data were collected on these main constructs and related influential constructs from 239 accounting and auditing directors in Amman Stock Market. Structural equation modelling was used to test the relationships simultaneously and to understand the predictive behaviour of the various attributes. Results revealed a strong relationship between the SysTrust's framework which has direct effect on business performance and the quality of financial reporting.